The Role of Sharia Economic Stakeholders in Indonesia’s Sharia Economy Masterplan 2019-2024: Pentahelix Concept Analysis - Ma'ruf, Aminudin; Mellinia, Rashifahunnisa’; Rohmaningtyas, Nurwinsyah; Alam, Shahbaz (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
Indonesia's Sharia economy has grown rapidly in recent years, attracting the attention of investors both domestically and internationally. In 2019, the Indonesian government launched the Sharia Economic Masterplan 2019-2024 to strengthen the Islamic economic ecosystem and position Indonesia as the world's leading Islamic economic center. This study aims to analyze the role of each Islamic economic stakeholder in the 2019-2024 Indonesian Islamic Economics Masterplan using the Pentahelix concept analysis. The results show that the government plays a crucial role as a regulator in formulating policies and regulations that support Islamic economic development. Through research and public consultation, academics contribute relevant concepts and innovations to the development of the Islamic economy. Islamic business people and financial institutions, such as Islamic banking, Islamic capital markets, and MSMEs, play an essential role as drivers of the halal industry. The Islamic economic community acts as an accelerator in strengthening the halal industry in various sectors. Meanwhile, as a multiplier, the media plays an essential role in maximising the fulfillment of the halal market share by promoting and educating the public about the available halal products and services. It is hoped that the synergy between stakeholders can achieve inclusive, sustainable sharia economic growth and encourage the progress of the halal industry in Indonesia.